Implementasi Pendidikan Multikultural melalui Aktivitas Tari Tradisional di MAN Sibolga - Azizah Hanum OK; Suwanto Suwanto; Jahrul Sihotang (Fakultas Tarbiyah dan Kegurusn Universitas Islam Bandung, 2025)
Dance is an art form that contains a cultural encyclopedia. Traditional dance in Indonesia represents Indonesia's multicultural society, as it embodies philosophical messages, encompassing spiritual, moral, and social aspects of its supporters. This study describes how promoting cultural and religious diversity through traditional dance activities at Sibolga State Islamic Senior High School (Madrasah Aliyah Negeri Sibolga) benefits multicultural education for students. The goal is to explain the meaning of cultural and religious diversity as something beneficial for local, national, and global life. Through the promotion of traditional dance at Sibolga State Islamic Senior High School, students can create and appreciate traditional dance. It is hoped that students will learn about the richness of their own region's traditional dances and learn about cultural differences between regions. Thus, they will become individuals who can respect diversity and accept the reality of cultural and religious diversity in Indonesia.